Uji Ketahanan Bakteri Patogen yang Diinokulasi pada Bakasang dalam Kondisi Lingkungan Berbeda - Indah Widyayanti; Melisa Masengi (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2019)
Bakasang is a fermented product, usually made from tuna fish offal or small fish such as anchovies and sardines, traditionally processed. This study aims to determine the resistance of pathogenic bacteria Salmonella typhi and Staphylococcus aureus which are inoculated in bakasang under different environmental conditions. Tests were carried out under different environmental conditions, such as pH 4.90, 5.05, 6.02 and 7.0, inokulum concentrations of 104 and 108 cells / ml, age of pathogenic bacteria culture 18 and 96 hours, temperature of 62 and 720C, and concentrations of bakasang: water (100 : 0, 50:50, and 25: 75). Data were analyzed using analysis of variance and t test. The results showed that pH 4.90 and 5.05 had a significant effect on the growth of S.typhi and S. aureus bacteria inoculated in bakasang (P <0.05). Concentration of inokulum 104 and 108. cells / ml, age of pathogenic bacteria culture 18 and 96 hours and concentration of bakasang: water gave no significant effect on the growth of pathogenic bacteria inoculated in the pair (P> 0.05). The results of the heat resistance of inoculated bacteria in the bakasang showed that the heating temperature of 62 and 72 ºC had a significant influence on the growth of pathogenic bacteria S. aureus and S. typhi which were inoculated in the pair (P <0.05).